Odpowiedzi

Najlepsza Odpowiedź!
2010-03-23T18:26:02+01:00
-3X=2x-10
- 3x - 2x = - 10
- 5x = - 10
x = 10/5 = 2
2x-2+7-x - brak znaku równości , wpisz to ci zrobię
10=4-2x
- 2x = 4 - 10
2x = 6
x = 6/2 = 3
0,5y=7-3y
3y + 0,5y = 7
3,5y = 7
y = 7/3,5 = 2
-(2x-1)=4
- 2x + 1 = 4
- 2x = 4 - 1 = 3
x = -3/2
2(x+1)=x
2x + 2 = x
2x - x = - 2
x = - 2
9(x+8)=9x+8
9x + 72 = 9x + 8
9x - 9x = 8 - 72
0 = - 64 - sprzeczne
2t-(3t+1)=6
2t - 3t - 1 = 6
- t = 6 + 1 = 7
t = - 7
-(4+x)=2(3-x)
- 4 - x = 6 - 2x
2x - x = 6 + 4 = 10
x = 10
4(a-1)=6(1+a)
4a - 4 = 6 + 6a
4a - 6a = 6 + 4
- 2a = 10
a = - 10/2 = - 5
3(y+6)-y=2(y+9)
3y + 18 - y = 2y + 18
3y - 2y - y = 18 - 18
0 = 0
(x-7)-2(3X+5)=3
x - 7 - 6x - 10 = 3
- 5x = 3 + 10 + 7
- 5x = 20
x = - 20/5 = - 4

1 5 1